2017
DOI: 10.1038/ncomms15628
|View full text |Cite
|
Sign up to set email alerts
|

JunB is essential for IL-23-dependent pathogenicity of Th17 cells

Abstract: CD4+ T-helper cells producing interleukin-17 (IL-17), known as T-helper 17 (TH17) cells, comprise heterogeneous subsets that exhibit distinct pathogenicity. Although pathogenic and non-pathogenic TH17 subsets share a common RORγt-dependent TH17 transcriptional programme, transcriptional regulatory mechanisms specific to each of these subsets are mostly unknown. Here we show that the AP-1 transcription factor JunB is critical for TH17 pathogenicity. JunB, which is induced by IL-6, is essential for expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 53 publications
(116 reference statements)
3
83
1
Order By: Relevance
“…For example, Nr4a2, Junb, and Fosl2 were among the 528 genes that were substantially enriched in siIEL CD8 + T cells relative to splenic cells at all time points following infection, and we found that knockdown of Nr4a2 or Junb resulted in impaired TRM cell differentiation. Junb and Fosl2 encode for AP-1 dimerization partners that have been reported to repress T-bet expression in Th17 cells (46,53). Given that downregulation of T-bet expression is important for early establishment of the TRM cell transcriptional program (17), it is tempting to speculate that In addition to identifying specific putative regulators of TRM cell differentiation, our analyses have implicated new pathways that may control aspects of TRM cell biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Nr4a2, Junb, and Fosl2 were among the 528 genes that were substantially enriched in siIEL CD8 + T cells relative to splenic cells at all time points following infection, and we found that knockdown of Nr4a2 or Junb resulted in impaired TRM cell differentiation. Junb and Fosl2 encode for AP-1 dimerization partners that have been reported to repress T-bet expression in Th17 cells (46,53). Given that downregulation of T-bet expression is important for early establishment of the TRM cell transcriptional program (17), it is tempting to speculate that In addition to identifying specific putative regulators of TRM cell differentiation, our analyses have implicated new pathways that may control aspects of TRM cell biology.…”
Section: Discussionmentioning
confidence: 99%
“…Nr4a2 is an orphan nuclear receptor that belongs to the Nr4a family of transcription factors, plays a central role in the development of regulatory T cells as well as pathogenic Th17 cells (40)(41)(42)(43), and has been implicated as an important driver of exhaustion in CD8 + T cells (44). Junb plays important roles in regulating Th17 cell identity and pathogenicity (45,46), and has also been implicated as part of the effector CD8 + T cell transcriptional program (35). Neither Nr4a2 nor Junb have previously reported roles in the differentiation of TRM cells.…”
Section: Shared and Tissue-specific Components Of Gene Expression Promentioning
confidence: 99%
“…Based on gene expression and motif analyses, it was proposed that several AP-1 TFs – including JunB and JunD – might be broadly important in regulating tissue-specific transcription in Tregs, particularly in the VAT and colon 6 . Previously, we and others found that the AP-1 TF JunB was essential for the differentiation of inflammatory T-helper 17 (Th17) cells 14, 15, 16 , demonstrating that JunB plays subset-restricted roles in T cell programming. More recently, JunB was reported to control differentiation and suppressive functions of eTregs 17 ; however, many of the conclusions from this study are confounded by the use of a CD4-cre-mediated Junb conditional deletion strategy that has since been demonstrated to cause cell-extrinsic defects in Treg development 18 .…”
Section: Introductionmentioning
confidence: 93%
“…Signal transducer and activator of transcription (STAT) 3 is another transcription factor regulating RORγt, and IL-17A (56) by interacting with the Stat-binding domains into the Rorc first intron, the Il17a promoter, and the intergenic region of the Il17a locus (Figure 1) (56)(57)(58). Moreover, STAT3 regulates positive epigenetic modifications, increasing permissive H3K4me3 marks on its target genes, including Rorc, Rora, and another gene encoding for transcriptional regulator of Th17 cells, called basic leucine zipper ATF-like transcription factor (BATF) (56).…”
Section: Other Transcriptional Regulators Of Rorc and Il17amentioning
confidence: 99%
“…Genome-wide JunB-DNA binding analysis, using ChIP sequencing with anti-JunB antibody, revealed that JunB colocalizes in Th17 cells with another transcription factor, called interferon regulatory factor (IRF)4, involved in Th17 differentiation (21). In fact, IRF4 targets sequences enriched for activating protein 1 (AP-1)-IRF composite elements (AICEs) located into regulatory elements of the Il17a promoter (58,60), which are cobound by BATF, an AP-1 factor (61). Thus, IRF4 and BATF bind cooperatively to structurally divergent AICEs to promote IL-17A activation in Th17 cells (61).…”
Section: Other Transcriptional Regulators Of Rorc and Il17amentioning
confidence: 99%